Pengaruh Media Flipbook Terhadap Kemampuan Menulis Teks Prosedur Siswa Kelas V Gugus VIII Kota Bengkulu - Azaria, Fidela Yolanda; Yuliantini, Nani; Ariffiando, Nady Febri (Universitas Bengkulu, 2024)
This study aims to find out the influence of flipbook media on the procedural text writing skill of fifth grade students in cluster VIII Bengkulu City. This research was quantitative research with quasi-experimental research methods and the type of design The Matching Only Pretest-Posttest Control Group Design. The population in this study was fifth grade students in cluster VIII Bengkulu City. The sample was a student of SDN V grade 34 Kota Bengkulu as an experimental class and students of VB SDN 36 Kota Bengkulu as a control class obtained through a cluster random sampling. The data collection technique were pre-test and post-test which were designed in the form of essay question with indicators of suitability of content, structure, writing rules and linguistic characteristic. The results showed that thitung > ttable (3,243 > 2,015) and Sig.(2-tailed) 0.002 < 0.05. This data suggests that there are significant differences in the procedural text writing skill in the experimental group and the control group due to the different treatment of the two classes, by using the flipbook media on experimental groups and not using flipbook media on control groups. Based on the results of the study, it can be concluded that Ha was accepted, which means there was an influence of flipbook media on the procedural text writing skill of fifth grade students in cluster VIII Bengkulu City.